2009
DOI: 10.1016/j.physbeh.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate intake of sweeteners on metabolic health in the rat

Abstract: The rise in prevalence of obesity, diabetes, metabolic syndrome, and fatty liver disease has been linked to increased consumption of fructose-containing foods or beverages. Our aim was to compare the effects of moderate consumption of fructose-containing and non-caloric sweetened beverages on feeding behavior, metabolic and serum lipid profiles, and hepatic histology and serum liver enzymes, in rats. Behavioral tests determined preferred (12.5–15%) concentrations of solutions of agave, fructose, high fructose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
(50 reference statements)
1
28
0
5
Order By: Relevance
“…Recent studies confirm changes in plasma lipid profile, with no apparent weight gain after 10 weeks of intermittent access to fructose solution 12.5% [21]. Body fat gain can lead to chronic changes in leptin and insulin sensitivity, through the loss of hormonal satiety signals [22,23,24].…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies confirm changes in plasma lipid profile, with no apparent weight gain after 10 weeks of intermittent access to fructose solution 12.5% [21]. Body fat gain can lead to chronic changes in leptin and insulin sensitivity, through the loss of hormonal satiety signals [22,23,24].…”
Section: Discussionmentioning
confidence: 96%
“…4 The juice from the agave plant is heated or enzymatically treated to hydrolyze the complex carbohydrates to sugars, and then it is concentrated into a syrup. 5 During the cooking process, much of the inulin, the principal polysaccharide from the agave core, is enzyme or acid hydrolyzed and converted to free sugars, mainly fructose. 6,7 Due to the high concentration of fructose (typically 90%), agave nectar is often advertised as a low glycemic option to refined sugar and marketed toward diabetics.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Due to the high concentration of fructose (typically 90%), agave nectar is often advertised as a low glycemic option to refined sugar and marketed toward diabetics. 5 However, research supporting the beneficial health benefits of agave nectar is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that de novo hepatic lipogenesis is increased with a high consumption of this monosaccharide (FAO 1998;Ouyang et al 2008). In murine models, it has also been observed that the lipid and liver metabolism changes indicate that even moderate fructose consumption might contribute to the onset or development of the metabolic syndrome, independently of significant effects on body weight (Figlewicz et al 2009). Nevertheless, there is also some evidence that the consumption of fructose with fruits or honey does not produce the same adverse metabolic effects as added fructose.…”
mentioning
confidence: 99%